Pengaruh Ownership Concentration terhadap Kinerja Operasional Perbankan di Indonesia - Widyarini, Maria; Octaviani, Yovita Pooy (Jurnal Administrasi Bisnis, 2012)
Based on Good Corporate Governance implemented by go public company espe-cially in banking industry which is one of the most affecting sectors in Indonesianeconomy, ownership concentration and banking operational performance are interre-lated. The purpose of this research is to analyze and interpret the effect of ownershipconcentration to the banking operational performance in Indonesia using the finan-cial data report such as Income Statement, Balance Sheet, and Stockholder Equity.The conclusion of this research are the state-owned banks have significant effect ofthe ownership concentration to operational performance; and inversely compared tothe private banks which have no significant effect of ownership concentration to theoperational performance. This can be seen from the ROE (Return on Equity) of thesebanks. Therefore, It is recommended to the banks (state-owned and private banks) toenhance the operational performance because will gives significant effect in the longterm as well. Moreover, the operational performance is one of a measure instrumentfor consumers prevalence (individual or corporation) in pointing of for their assetsafety.Keywords: Good corporate governance, ownership concentration, operationalperformance